Self-stigma among people living with HIV/AIDS: revisiting human rights values for inclusive health service - Nur Faizah, Ida; Cuyno Mellen, Renie; Syafriani, Syafriani; Wijayanti Subronto, Yanri; Hasanbasri, Mubasysyir; Siwi Padmawati, Retna (BKM Public Health and Community Medicine, 2021)
Purpose: This study explores self-stigma in people living with HIV/AIDS (PLHIV) who used Puskesmas services in Yogyakarta and its impact on their health service access. Method: Data come from in-depth interviews with three PLHIVs (one male and two female). Results: Self-stigma occurs among the respondents at the first diagnosis as HIV positive. Self-stigma is triggered by wrong judgments about HIV disease from health workers and communities. Self-stigma is based on negative thoughts of feeling different, having exclusivity (different from their environment). Thus, it is easier to feel rejected, showing the worst if they are discriminated against. The first thought when the respondent was diagnosed with positive HIV was, “how do I die? How will I die tomorrow?” "Not expect, why should I?" "My world has been destroyed; I have no hope anymore.” Feeling of vulnerability and helplessness related to death and illness trigger hypersensitive responses, so they tend to withdraw from social relationships. Continuous exposure will result in a reluctance to access health services due to decreased motivation for treatment. Conclusions Self-stigma is a defense mechanism to fight stigma and discrimination. Hypersensitivity protects to anticipate rejection from the surrounding environment. Thus, PLWHA understands disclosure to reveal the status or not to the closest people. However, this condition needs to be regulated so that self-stigma does not develop to interfere with life functions such as social relations, economy, and work. Self-stigma can reduce treatment prognosis and increase comorbidity and mortality due to lack of a support system, decreased treatment motivation. Therefore, Puskesmas should collaborate with families and communities. Puskesmas can create volunteer groups from people with stigmatized diseases as agents of change to build trust between PLWHA, families, and health workers. For suggestion, meetings with patients as well as an activity to support human rights in celebration day to develop equal and acceptance feelings.